Psychological Resilience of Personality as a Basis of Subject's Self-Realization - S I Kudinov; Suad M Hammad (Peoples' Friendship University of Russia (RUDN University), 2015)
The article presents the psychological approaches in Russia, considering the interaction between man and environment, the question of the ability to resist the negative impact of the external environment and the successful resolution of the vital tasks.